การพัฒนาตัวบ่งชี้คุณลักษณะเด็กที่มีพรสวรรค์ - สุปราณี บุระ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this research were: 1) to analyze the factor loadings of factors and indicators of gifted children’s characteristics and 2) to develop a model for the gifted children’s characteristics and examine the consistency between the developed model and empirical data. The research sample was carried out among 335 teachers and parents of students in grade 4 – 6. This event to identify gifted children was organized by the Institute for Gifted and Innovative learning at the GTX center. The variables were the factors and indicators of gifted children’s characteristics. The factors consist of intelligence, creativity, and emotional and social behavior. Each factors had 10, 4 and 12 indicators respectively. The data was collected using scheduled interviews about factors and indicators and questionnaire. Descriptive statistics, t – test, Pearson’s product moment correlation coefficient were analyzed by SPSS program. Whereas the second order confirmatory factor was analyzed by LISREL program. The major findings were as follows: 1. The standard factor loadings of 3 factors consist of intelligence, creativity, and emotional and social behavior. Each factor had 0.969, 0.959 and 0.916 respectively. With such a high level and with the vicinity at 0.01 significant level. Each indicator consist of the following factors: 1.1 Factor in intelligence: each indicator had standard factor loadings between 0.470 – 0.778. The highest standard factor loadings indicators were ability in analytical thinking, ability in problem solving, ability in think out of the block, ability in logical thinking, ability in comment and evaluation, ability in rapid learning and understanding, ability in memory, ability in sign and numeral recognition, ability in synthetic thinking and ability in abstract thinking respectively. 1.2 Factor in creativity: each indicator had standard factor loadings between 0.705 – 0.833. The highest standard factor loadings indicators were ability in flexibility, ability in elaboration, ability in fluency and ability in originality respectively. 1.3 Factor in emotional and social behavior: each indicator had standard factor loadings between 0.520 – 0.746. The highest standard factor loadings indicators were self confidence, leadership ability, to be inquisitive and to observe, have system to work, good relationship with adult, to attempt, to be careful, good thinking with social and environment, like intellectual activity, like freedom, enthusiastic and concentration respectively. 2. A model for the gifted children’s characteristics was validated and fitted to the empirical data with X2 = 281.226, p = 0.061, df = 246, GFI = 0.939, AGFI = 0.913 and RMR = 0.014.